Analgesic drug development: proof-of-mechanism and proof-of-concept in early phase clinical studies - Hemme J. Hijma, MSc; Geert Jan Groeneveld, MD, PhD (Elsevier, 2021)
Effective treatment for many pain disorders is still lacking, which is due to the complexity of pain in general and of the underlying pathology of many pain syndromes in particular. This results in the majority of investigational analgesic drugs failing to reach registration, either due to lack of efficacy, or due to the drug's adverse effect profile. To increase the number of analgesics that reach the patient, it is essential to carefully and rationally plan the clinical development program. By including proof-of-mechanism (PoM) and/or proof-of-concept (PoC) methods in early-phase clinical drug studies, the analgesic drug developer will be better informed regarding the key characteristics of the studied drug, which will aid in making crucial decisions during the development process. Here, we describe the top 10 currently most developed analgesic drug classes, link them mechanistically to appropriate methods to demonstrate PoM and PoC in early-phase clinical trials, and include pros and cons of each of the methods described. Lastly, we discuss how each analgesic drug class requires a tailored experimental approach for proper evaluation of PoM and PoC, and how this can contribute to an efficient and question-based approach in early-phase analgesic drug research.